RESEARCH FEATURES AND EFFICIENCY OF ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH METABOLIC DISORDERS - E. I. Polozova; E. I. Polozova; E. V. Puzanova; A. A. Sesekina; I. S. Ovsyannikova; E. N. Domina; I. A. Surkova (Евразийский Кардиологический Журнал, 2019)
Cardiovascular disease (CVD) is an urgent problem of world and national medicine. The leading place among this pathology belongs to arterial hypertension (AH). The prognosis becomes even more unfavorable when combined with AH metabolic disorders. The number of patients with metabolic syndrome (MS) is projected to exceed 500 million by 2025. In patients with MS, the frequency of sudden death and CVD increases 2-4 times, the risk of coronary heart disease is 3-4 times higher, and the risk of ischemic stroke is 2 times higher. The risk of formation of type 2 diabetes increases 5-9 times. AH is one of the components of MS and is observed in more than half of patients. Target organs in such patients are affected much earlier and their changes are much more pronounced than in patients with hypertension without MS. We set a goal to study the effectiveness of treatment of arterial hypertension in patients with metabolic syndrome who were on inpatient treatment in the therapeutic Department of GBUZ RM «Republican clinical hospital №5» in Saransk in 2017-2018.